PERAN PENYULUH AGAMA ISLAM DALAM PRAKTEK PERAWATAN JENAZAH BAGI MAJELIS TAKLIM NURUL HIDAYAH DI DESA LAMBAI KECAMATAN LAMBAI KABUPATEN KOLAKA UTARA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
The main problem is “What is the role of Islamic religious counselors in the practice of corpse care for the Nurul Hidayah Taklim Assembly in Lambai Village, Lambai District, North Kolaka Regency with the formulation of the problem?”1. How are the Efforts of Islamic Religious Counselors in Guiding the Practice of Corpse Care for the Nurul Hidayah Taklim Assembly in Lambai Village, Lambai District, North Kolaka Regency, 2. What are the results of corpse care practices for the Nurul Hidayah Taklim Assembly in Lambai Village, Lambai District, North Kolaka Regency? The researcher used a descriptive qualitative research type, which was located in Lambai Village, Lambai District, North Kolaka Regency. The primary data source is the Islamic Religious Counselor Mariama, as a key informant, and additional informants, namely, Basse Marwati, Nuryatim, Buatimo, Nartin, Juwita, Musnidar, and Nirwana. The Guidance Approach used in this context involves religious aspects using theories based on Islam. Then the secondary data sources are books, journals, articles, and banners. Data collection methods are observation, interviews, and documentation. The data analysis techniques used by researchers are data reduction, data presentation, and drawing conclusions.  The results of this study indicate that the efforts of Islamic religious counselors in the practice of corpse care for the Nurul Hidayah Taklim Assembly in Lambai Village, Lambai District, North Kolaka Regency: 1. Explaining the stages of preparation of personnel mental and spiritual preparation, 2. Explaining the procedures of bathing the corpse, 3. Conveying the procedures for praying for the corpse, 4. Conveying how to bury the corpse. The results of the practice of corpse care for the Majelis Taklim Nurul Hidayah in Lambai Village are 1. Understanding the preparation stage, 2. Understanding the stage of procedures for bathing and shrouding the corpse, 3. Being able to pray for the corpse, and 4. Being able to bury the corpse. The implications of this study are: 1. For Islamic religious counselors in Lambai Village, they are always ready to provide training and motivate the people of Lambai Village regarding corpse care. 2. For the Majelis Taklim Nurul Hidayah, to have an awareness of the importance of carrying out fellow human duties such as corpse care, which is a noble task and has its own reward in the sight of Allah swt.